Recent advances in coaxial electrospun nanofibers for wound healing - Jing Zhao; Liyun Chen; Aiwei Ma; Xujue Bai; Yating Zeng; Daojun Liu; Bo Liu; Wancong Zhang; Shijie Tang (Materials Today Bio)
The skin is the body's primary immune barrier, defending it against pathogenic invasion. Skin injuries impose a significant physiological burden on patients, making effective wound management essential. Dressings are commonly employed in wound care, and electrospun nanofiber dressings are a research hotspot owing to their ease of fabrication, cost-effectiveness, and structural similarity to the extracellular matrix. Coaxial electrospinning offers considerable advantages in drug delivery, fiber structure transformation, and enhanced interaction with the host. These attributes make coaxial electrospun materials promising candidates for precision and personalized wound dressings in medical treatments. This review provides a comprehensive overview of wound healing and its influencing factors. It also outlines coaxial electrospinning's production principles and benefits in wound dressings. Guided by the factors affecting wound healing, coaxial electrospun nanofiber dressings have different application modalities. Furthermore, we discuss the current limitations and future directions for enhancing the current coaxial electrospun dressing technologies.